Managing the attitudes of breast cancer patients towards physical activity in a multicultural environment - Malchrowicz-Mośko, Ewa (Quality in Sport, 2022)
Based on a review of literature, the article presents the main problems and barriers in the diagnostics, treatment and prevention of breast cancer among women representing various cultures, mainly those following Islam and Hinduism. Hospitals and oncology centers that serve diverse populations should consider the religious needs of female breast cancer patients which have been described in this paper. The burden of breast cancer continues to increase in low- and middle-income countries, where women present with more advanced disease and have worse outcomes compared with women from high-income countries. Moreover, lifestyle-associated factors play an important role in prevention of such malignancies as breast cancer. Physical activity before, during and after diagnosis improves outcomes for breast cancer. Unfortunately, few Muslim women have opportunities to participate in regular exercises which are recommended by World Health Organization for breast cancer survivors.